Selective photoinactivation of Candida albicans in the non-vertebrate host infection model Galleria mellonella - Chibebe Junior, Jose [UNESP]; Sabino, Caetano P.; Tan, Xiaojiang; Junqueira, Juliana C. [UNESP]; Wang, Yan; Fuchs, Beth B.; Jorge, Antonio O. C. [UNESP]; Tegos, George P.; Hamblin, Michael R.; Mylonakis, Eleftherios (Biomed Central Ltd., 2013)
Background: Candida spp. are recognized as a primary agent of severe fungal infection in immunocompromised patients, and are the fourth most common cause of bloodstream infections. Our study explores treatment with photodynamic therapy (PDT) as an innovative antimicrobial technology that employs a nontoxic dye, termed a photosensitizer (PS), followed by irradiation with harmless visible light. After photoactivation, the PS produces either singlet oxygen or other reactive oxygen species (ROS) that primarily react with the pathogen cell wall, promoting permeabilization of the membrane and cell death. The emergence of antifungal-resistant Candida strains has motivated the study of antimicrobial PDT (aPDT) as an alternative treatment of these infections. We employed the invertebrate wax moth Galleria mellonella as an in vivo model to study the effects of aPDT against C. albicans infection. The effects of aPDT combined with conventional antifungal drugs were also evaluated in G. mellonella.Results: We verified that methylene blue-mediated aPDT prolonged the survival of C. albicans infected G. mellonella larvae. The fungal burden of G. mellonella hemolymph was reduced after aPDT in infected larvae. A fluconazole-resistant C. albicans strain was used to test the combination of aPDT and fluconazole. Administration of fluconazole either before or after exposing the larvae to aPDT significantly prolonged the survival of the larvae compared to either treatment alone.Conclusions: G. mellonella is a useful in vivo model to evaluate aPDT as a treatment regimen for Candida infections. The data suggests that combined aPDT and antifungal therapy could be an alternative approach to antifungal-resistant Candida strains.
Keywords: Candida albicans; Photodynamic therapy; Galleria mellonella